Stress, and Mental Health Problems in Gifted Adolescents and the role of ICTs - Alexopoulou, Arhondoula; Batsou, Alexandra (Eximia, 2023)
There has been an open-ended, continuing argumentation whether giftedness is associated with excessive stress burden or mental disorders. Various literature reviews and research articles exist on the subject, however, there has been little outcome concerning direct comparisons among gifted and non-gifted young people. Contemporary research still presents findings which support both views. In the present review, there has been made an attempt to provide a scientific perspective of research related to emotional problems and/or mental disorders of gifted adolescents. We included research concerning depression and suicidal behaviour, and studies which offer ample evidence on the way stress and anxiety are created, and function in gifted young people. We rather concentrated on research and articles focusing on examining gifted young adolescents in comparison with the general, non-gifted population of the same age. The present review has been limited to research published within the past twenty years (2000-2019).